PENERAPAN PEMBELAJARAN BLENDED LEARNING MENGGUNAKAN APLIKASI GOOGLE CLASSROOM UNTUK MENINGKATKAN HASIL BELAJAR - Raden Achmad Djauhari (saintifika, 2021)
Abstract: This research is a qualitative descriptive study aimed to describe the upgrading student learning outcomes on the subject of phytagoras class VIII E SMPN 1 Jember. The learning is done by applying blended learning with google classroom aplication. This study is a Classroom Action Research, which consists of 2 cycles and 4 learnings. Each cycle consists of four stages: planning, action, observation, and reflection. Student learning outcomes obtained based on the value of the test conducted at the end of each cycle. Based on tests carried out, of the 32 students of class VIII E, there are 19 students who otherwise has been thoroughly studied in cycle 1 with a percentage of 59,75% . Better results are obtained in cycle 2 with completeness percentage of 87,5%. Thus, it can be conclude that done by applying blended learning with google classroom aplication can improve student learning outcomes